Hate speech in social media - Sadaf, Shomaila (2020)
Social networking sites (SNS) play a substantial role in facilitating online communication and social interaction a global scale. Simultaneously, these social networks become platforms that not only spread the rhetoric of hate but also normalize it. This study systematically uncovers the existing literature related to hate speech in social media. The focus of this study is to explore the approaches used in data collection and data analysis along with theoretical frameworks used in the existing studies. The method used in this study is a systematic literature review, and a total of 30 articles met the inclusion criteria and are used for the final analysis. The findings related to data collection and data analysis methods show that the most common data collection method is that, the data is taken directly from online social networks in the form of user comments, content shared on these networks, tweets, blog posts, etc., while the quantitative data is collected through surveys and questionnaires. Analysis further show that the qualitative studies provide in-depth descriptive analysis of the discourses online, whereas few studies used quantitative data analysis methods. The two most common areas of research on hate speech online according to the analysis are political and ethnic/racial issues. A total of 17 studies out of 30 used theories or models to support their central ideas. The present study further aims at exploring the use of positioning theory with regard to hate speech in social media. The analysis reveals that only one study has used positioning theory as the theoretical base, and only one article utilized the idea of positioning analysis as a discursive process at various levels. Considering the basic aim of this study, important data is gathered within the area of hate speech in social media and information is extracted that would help in exploring various other areas for future research.